2021
DOI: 10.3390/molecules26030727
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Prophylaxis Efforts Based on Natural Antiviral Plant Extracts and Their Compounds

Abstract: During the time of the novel coronavirus disease 2019 (COVID-19) pandemic, it has been crucial to search for novel antiviral drugs from plants and well as other natural sources as alternatives for prophylaxis. This work reviews the antiviral potential of plant extracts, and the results of previous research for the treatment and prophylaxis of coronavirus disease and previous kinds of representative coronaviruses group. Detailed descriptions of medicinal herbs and crops based on their origin native area, plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 153 publications
0
25
0
3
Order By: Relevance
“…Naja ve Hamdeh (2020), pandemi sürecinde bireysel, sosyal ve milli seviyelerde optimal beslenmeyi destekleyen çok seviyeli aksiyon planı belirlemişlerdir. Bu çalışmada asıl amaçlar, sağlıklı beslenmenin sürdürülmesi ve aynı zamanda kullanılabilen tüm bitkisel ürünler ile bitki türevleri hakkında kapsamlı bir bilimsel veri tabanının oluşturulmasına yöneliktir [6].…”
Section: Bitkisel Sekonder Metabolitlerin Kullanımı Ve Covid-19 Ile Mücadeleunclassified
See 2 more Smart Citations
“…Naja ve Hamdeh (2020), pandemi sürecinde bireysel, sosyal ve milli seviyelerde optimal beslenmeyi destekleyen çok seviyeli aksiyon planı belirlemişlerdir. Bu çalışmada asıl amaçlar, sağlıklı beslenmenin sürdürülmesi ve aynı zamanda kullanılabilen tüm bitkisel ürünler ile bitki türevleri hakkında kapsamlı bir bilimsel veri tabanının oluşturulmasına yöneliktir [6].…”
Section: Bitkisel Sekonder Metabolitlerin Kullanımı Ve Covid-19 Ile Mücadeleunclassified
“…), zeytin yaprağı (Olea europea L.), meyan kökü (Glyrrhiza glabra L.) ve farklı kekik cinslerinin (Origanum, Thymus ve Thymbra) Covid-19 tedavisi için potansiyele sahip olarak görülmektedir [15]. Özellikle terpenoitler, alkaloitler, stilbenler ve flavonoitlerin bitkisel bazlı anti-viral ilaçların üretilmesi için temel biyolojik aktiviteye sahip metabolitler oldukları düşünülmektedir [6]. Şimdiye kadar; arktin, skutelarin, forsitozit, kaempferol, sekoksiloganin, nikotianamin, saikosaponin gibi çeşitli fitokimyasal bileşiklerin anti-SARS-CoV-2 aktivitesine sahip oldukları bildirilmiştir [8] (Tablo 3).…”
Section: Bitkisel Sekonder Metabolitlerin Kullanımı Ve Covid-19 Ile Mücadeleunclassified
See 1 more Smart Citation
“…According to their findings, the highest antibacterial activity was observed for acetone and the lowest antibacterial activities were observed for isopropyl alcohol, and petroleum ether extracts against Proteus mirabilis. Interestingly, in a recent review in 2021 stated that Clitoria ternatea plant extracts contain antiviral potential and can be used for COVID-19 prophylaxis efforts based on natural antiviral Plant extracts and their compounds [23]. At the same time, it is worth mentioning here that in Srilankan traditional medicine treatment regime Clitoria ternatea has been mentioned as a suitable plant to treat rabies as well [9].…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…Rios and Reco, 2005, observed that the interests of scientific community on healthcare applications of phytochemicals have been continuously increasing. [39,40] There is wide range of criteria that have been studied by the researchers. Many of them have focused on the antimicrobial properties of various extracts obtained from various parts of the plants based on traditional knowledge, folk medicines, essential oils, compounds isolated from plants, and various groups of phytochemicals such as flavonoids, terpenes, alkaloids, proteins, essential oils, and flavones.…”
Section: Qualitative Estimation Of the Various Extracts Preparedmentioning
confidence: 99%